On the importance of sectoral and regional shocks for price setting - Guenter W. Beck; Kirstin Hubrich; Massimiliano Marcellino (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2012)
We use a novel disaggregate sectoral euro area data set with a regional breakdown to investigate price changes and suggest a new method to extract factors from over-lapping data blocks. This allows us to separately estimate aggregate, sectoral, country-specific and regional components of price changes. We thereby provide an improved estimate of the sectoral factor in comparison with previous literature, which decomposes price changes into an aggregate and idiosyncratic component only, and interprets the latter as sectoral. We find that the sectoral component explains much less of the variation in sectoral regional inflation rates and exhibits much less volatility than previous findings for the US indicate. We further contribute to the literature on price setting by providing evidence that country- and region-specific factors play an important role in addition to the sector-specific factors, emphasising heterogeneity of inflation dynamics along different dimensions. We also conclude that sectoral price changes have a “geographical” dimension, that leads to new insights regarding the properties of sectoral price changes.
urn:nbn:de:hebis:30:3-268769
Keywords: E31; C38; D4; F4; 330; Disaggregated prices; euro area regional and sectoral inflation; common factor models